KONSTRUK EMOSI MARAH PERSPEKTIF AL-QUR’AN - Miftah Ulya (el-'Umdah, 2020)
Emotional anger is an urgent and has an essential role in living human life, besides he is also praiseworthy as well as the nature and attitude to watch out for, because anger is also the most active role in things that are self-preservation, family, and other social communities. Anger emotions arise as a result of feelings of displeasure with people other than themselves, or certain objects that are closely related to the personality and inner experience experienced by someone. In the Qur'an the expression "human emotion" is very closely related to human behavior personally related to information aspects of the past, present or future. In the Koran no less than 13 times in the form of unequal derivatives, where anger is depicted and seen in human attitudes and behaviors that sometimes appear on the face, can be detected in verbal and nonverbal forms, angry with fa'ali, angry with the qalb fil , angry in terms of quelling evil and angry in terms of human expectations that are not achieved.Humans are required to know and minimize the nature of anger because of the impact it has on the lives of human beings both psychologically, sociologically and psychologically. But through the media remember Allah Almighty, through purification media with the nature of Husn al-zhan, patience, gratitude, forgiveness is a solution in controlling human angry emotions